Game Avoid Viruses: Pengembangan Game Edukasi 3D Unity Berbasis Arcade - giriwahyuwiriasto; Chotibul Umam Wiranda (Depertment of Electrical Engineering University of Mataram, 2023)
This research aims to develop an educational game using Unity 3D. The game is designed to provide an enjoyable gaming experience while imparting an understanding of the importance of maintaining health and preventing the spread of viruses. We used Unity 3D as the primary development platform and implemented gameplay mechanics involving a player character who must avoid viruses descending from the top of the screen. The development method includes level design, character control implementation, and providing visual and audio feedback to the player. Evaluation was conducted through internal testing and gathering feedback from users. The results showed that the game successfully provided an experience for users and also improved their understanding of the importance of avoiding the spread of viruses. This research contributes to the development of interactive educational games to support public health awareness efforts.